Historical and Sociological Review of the Development and Change of the Islamic Religious Education Curriculum in Indonesia - Nurhidaya M, Nurhidaya M; Syaifuddin, Syaifuddin; Mumtahanah, Mumtahanah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The intensity of cases of violence, drugs, sexual violence, anarchist demonstrations, and problems that hurt national education. One factor is the disorientation of PAI values in the Islamic education curriculum, which no longer emphasises divinity, humanity and nature. This research examines the development of the Islamic religious education curriculum in a historical and sociological review. The research method used is library research with content analysis, namely studying the development of the PAI curriculum with data sources based on literature, such as books, regulations, and scientific articles that examine the development of the PAI curriculum. The results of this research show that changes to the 1947-1968 curriculum and the Goal Achievement Oriented Curriculum, namely the 1975 curriculum and the 1994 curriculum; Competency-Oriented Curriculum, namely the 2004 competency-based curriculum (KBK), the Education Unit Level Curriculum (KTSP), and the 2013 curriculum. Based on a sociological review, curriculum changes are a norm of development over time; still, the penetration of PAI values such as divinity, humanity and nature in every change in the curriculum is relatively disorienting in practice.